2007
DOI: 10.2174/138920107780487500
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Resistance in Central Nervous System Tumors: From the Traditional Cell-Resistance Model to the Genetically Driven Approaches on Therapy

Abstract: The advances in the cure rates observed in the oncology field in the past decades were not fully assembled by primary brain tumors. In this heterogeneous group of diseases, resistance to either chemotherapy or radiotherapy still is a major problem to be addressed. Several genetic and epigenetic events may directly influence the response to treatment in these tumors. Throughout recent discoveries, drug resistance in brain tumors was better understood as a final product of different and complexes pathways that i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
0
3
0
1
Order By: Relevance
“…Previous reports have shown that MDR1 gene expression was not detected, or was only weakly detected in glioma cells, suggesting that P-gp contributes to cellular resistance in a mere small subgroup of gliomas, but contributes frequently in neuroblastomas and meningiomas. Other studies indicate that among glial tumours, grade I and II astrocytomas expressed the highest levels of P-gp, Mrp3 and lung resistance-related protein (LRP), and that these high levels of expression may be related to the primary resistance of low-grade gliomas to chemotherapy [36]. In contrast, Mrp1 was suggested to Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have shown that MDR1 gene expression was not detected, or was only weakly detected in glioma cells, suggesting that P-gp contributes to cellular resistance in a mere small subgroup of gliomas, but contributes frequently in neuroblastomas and meningiomas. Other studies indicate that among glial tumours, grade I and II astrocytomas expressed the highest levels of P-gp, Mrp3 and lung resistance-related protein (LRP), and that these high levels of expression may be related to the primary resistance of low-grade gliomas to chemotherapy [36]. In contrast, Mrp1 was suggested to Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Such is the cases of medulloblastomas and ependymomas [36]. Similarly, Mrp1 was frequently found to be overexpressed in a large proportion of non-small cell lung carcinoma (NSCLC) tumours prior to treatment exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Esses dados estão de acordo com a literatura, que mostra a progressão tumoral por ausência de resposta à terapêutica como principal desafio no tratamento dos tumores do SNC. [17][18][19] Os resultados desta casuística em relação à probabilidade de SGLO são inferiores aos descritos em estudos internacionais. Os resultados obtidos em estudos realizados nos Estados Unidos mostram índices de SGLO aos cinco anos de 66 a 75% para os tumores de SNC em conjunto.…”
Section: Resultsunclassified
“…More importantly, both imaging modalities detect tumor response much earlier than traditional methodologies that rely on macroscopic volumetric changes (Schepkin et al, 2006). Proteomics holds the promise of allowing a molecular understanding of the resistance of CNS tumors to chemotherapy and individualization of therapy (Valera et al, 2007a; Valera et al, 2007b). The potential already exists to use microarray and informatics technology to discern patterns of gene expression associated with chemoresistance and to discover novel mechanisms and effectors of such resistance (Bredel et al, 2004).…”
Section: Introductionmentioning
confidence: 99%